New Zealand : 2022 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
New Zealand's management of the pandemic, including health policy and macroeconomic policy support, has been effective in ensuring economic recovery. Output has already recovered to above potential, the labor market is tight, and inflation has risen to above the Reserve Bank of New Zealand's (RBNZ) target range.